Outcomes With Intermediate Left Main Disease: Analysis From the ISCHEMIA Trial. (22nd March 2022) - Bangalore, Sripal; Spertus, John A.; Stevens, Susanna R.; Jones, Philip G.; Mancini, G.B. John; Leipsic, Jonathon; Reynolds, Harmony R.; Budoff, Matthew J.; Hague, Cameron J.; Min, James K.; Boden, William E.; O'Brien, Sean M.; et al.
Abstract : Background: Patients with significant (≥50%) left main disease (LMD) have a high risk of cardiovascular events, and guidelines recommend revascularization to improve survival. However, the impact of intermediate LMD (stenosis, 25%–49%) on outcomes is unclear. Methods: Randomized ISCHEMIA (International Study of Comparative Health Effectiveness With Medical and Invasive Approaches) participants who underwent coronary computed tomography angiography at baseline were categorized into those with (25%–49%) and without (<25%) intermediate LMD. The primary outcome was a composite of cardiovascular mortality, myocardial infarction (MI), or hospitalization for unstable angina, heart failure, or resuscitated cardiac arrest. The primary quality of life outcome was the Seattle Angina Questionnaire summary score. Results: Among the 3699 participants who satisfied the inclusion criteria, 962 (26%) had intermediate LMD. Among invasive strategy participants with intermediate LMD on coronary computed tomography angiography, 49 (7.0%) had significant (≥50% stenosis) left main stenosis on invasive angiography. Patients with intermediate LMD had a higher risk of cardiovascular events in the unadjusted but not in the fully adjusted model compared with those without intermediate LMD. An invasive strategy increased procedural MI and decreased nonprocedural MI with no significant difference for other outcomes including the primary end point. There was no meaningful heterogeneity of treatment effect based on intermediate LMD status except for nonprocedural MI for which there was a greater absolute reduction with invasive management in the intermediate LMD group (−6.4% versus −2.0%; P interaction =0.049). The invasive strategy improved angina-related quality of life and the benefit was durable throughout follow-up without significant heterogeneity based on intermediate LMD status. Conclusions: In the ISCHEMIA trial, there was no meaningful heterogeneity of treatment benefit from an invasive strategy regardless of intermediate LMD status except for a greater absolute risk reduction in nonprocedural MI with invasive management in those with intermediate LMD. An invasive strategy increased procedural MI, reduced nonprocedural MI, and improved angina-related quality of life. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01471522.